THE IN(TER)DEPENDENCIES OF MOBILE ONLINE AND OFFLINE SPACES: REFLECTIONS ON METHODS, PRACTICES, ETHICS - Kaufmann, Katja; Palmberger, Monika; Parreiras, Carolina; Bussoletti, Arianna; Belotti, Francesca; Comunello, Francesca; Donato, Stellamarina; Wagenaar, Welmoed; Bermúdez, Juan; Schweiger, Moritz; Wimmer, Jeffrey (AoIR Selected Papers of Internet Research, 2021)
Mobile media technologies place users in digital (online) as well as physical (offline) spaces in novel ways, opening up new environments of affordances. In everyday life these mobile online and offline spaces are increasingly interdependent and interwoven in manifold ways. Practices, experiences, meanings and expectations are negotiated across these spaces, while at the same time they are bound by the respective logics and limitations, leading to new interrelations and contradictions. The mobile, interlocking but non-converging nature of these spaces involves issues of access and power in struggles over in(ter)dependencies and leads to significant method(odolog)ical, practical and ethical challenges for researchers, to which the current COVID-19 pandemic only adds complexity. Researchers are confronted with questions such as: What are appropriate designs to study mobile online and offline spaces and their intersections? Do interdependent spaces call for likewise interdependent methodological approaches? In what ways can elaborated mixed and multi-method designs capture complexity adequately without the researchers losing sight of the specifics? And what are the ethical and practical implications for the parties involved? Meanwhile, in the methodological literature, the specific challenges associated with researching the intersections of online and offline spaces, especially under mobile conditions, are rarely explicitly addressed. For this reason, the panel presents a thought-provoking range of five examples of research into phenomena at the intersections of mobile online and offline spaces and the associated experiences as well as methodological challenges of researchers in dealing with issues of in(ter)dependence at all levels.